TI_GERICHTE 12.2009.63 vom 16. Februar 2011 , Società semplice - vizi nella delibera assembleare - effetti - causa priva d'oggetto - stralcio - TI Tribunale d'appello (2011)
Società semplice - vizi nella delibera assembleare - effetti - causa priva d'oggetto - stralcio